Heat transfer coefficient determination on 3D geometries from transient thermochromic liquid crystal experiments - Ryley, J; McGilvray, M; Gillespie, D (American Institute of Aeronautics and Astronautics, 2019)
A valuable new postprocessing technique has been developed to enable the application of transient thermochromic liquid crystal experiments where lateral conduction is significant and thus cannot be treated as one-dimensional (1D). This enables the measurement of spatially resolved heat transfer coefficient (HTC) over geometrically complex surfaces, extending the current limitations of transient thermochromic liquid crystal experiments. The postprocessing technique couples raw experimental transient thermochromic liquid crystal data and finite element analysis, in an iterative procedure, to generate the HTC distributions. In the current study, the experimental data come from a stationary experiment of an engine realistic rib turbulated cooling passage. Spatially resolved maps of HTC have been determined over the surface of the ribs. The results are compared with conventionally processed experimental data that assume 1D semi-infinite conduction and also to results from steady-state numerical simulations. Where the 1D assumption is applicable, results are less than the experimental uncertainty (<6%) at the majority of locations. Typical 1D-based methods are unable to provide reliable spatial measurements over geometrically complex ribbed surfaces, and to the authors’ best knowledge this is the first time distributions of HTC have been reported for engine representative rib geometry.